Assessment of factors affecting innovation policy in biotechnology - Samira Khodi Aghmiuni; Saeed Siyal; Qiang Wang; Yuzhen Duan (Journal of Innovation & Knowledge (JIK), 2020)
Nearly three decades have passed since the new knowledge and technologies like genetics and biotechnology have emerged. By passing through various periods in which labor force, resources and capital, each one at a certain time, have been comparative and competitive advantages for a more powerful economy, biotechnology is one of the advanced technologies that countries are investing in, in order to achieve sustainable development in the current century. The capabilities of this knowledge are the creation of fundamental and gradual innovations, in addition to the several applications that generate wealth for countries. For this purpose, innovation policies in biotechnology have been addressed here. This study draws on the resource based theory and examines the research development polices, international-corporate collaboration policies and government supportive innovation policies. The statistical population of this study consisted of 165 responses from the directors and experts active in the field of biotechnology industry in Iran (pharmaceutical, food and agriculture). Research hypotheses were tested using SMART PLS software. The results of the research revealed that research development polices, international corporate collaboration policies and government supportive innovation policies have a significant impact on the development of biotechnology innovation activities. In addition, we have discussed the implications of the study as well as given some future directions.
Keywords: O02; O03; O04; L05; 650; Biotechnology; Government support; Innovation; Innovation policy